Epidemiological characteristics of 5838 cases of enterovirus infection in children in Hangzhou from 2018 to 2023 - Qun Lao; Xianyao Lin; Shu Teng; Zhenghong Qi; Xinfeng Zhao; Shiyong Zhao (Scientific Reports)
Abstract This study retrospectively explored the characteristics of 5838 children with enterovirus infection in our hospital from 2018 to 2023. In addition, children with enterovirus (EV: EV typing was performed using RT-PCR) infection exhibiting clinical manifestations of viral encephalitis were investigated. Pharyngeal swabs or fecal samples from outpatients and inpatients from our hospital were collected from 2018 to 2023 and were subjected to EV nucleic acid detection using real-time fluorescence quantitative PCR. Furthermore, cerebrospinal fluid EV nucleic acid detection was performed for children with clinical manifestations of viral encephalitis. Descriptive epidemiological methods were used to analyze the age, sex, and etiology of EV infection cases. Statistical analyses were performed with SPSS 20.0. The statistical data were expressed as percentages, and the χ2 test was used for statistical analysis. A total of 9676 children were included in this study, and 5838 (60.33%) showed positive EV nucleic acid test results. These included 1909 cases of Coxsackievirus group A type 6 (CV-A6) (32.70%), 259 cases of Coxsackievirus group A type 16 (CV-A16) (4.44%), 252 cases of Coxsackievirus group A type 10 (CV-A10) (4.32%), and 34 cases of enterovirus type 71 (EV-A71) (0.58%). A total of 3384 other uncategorized EVs (57.97%) were found. The detection rates of EV-A71 and CV-A16 decreased year by year, while the detection rates of other EV nucleic acids increased year by year. Cerebrospinal fluid (CSF) EV nucleic acid detection was performed on 1520 children with positive EV nucleic acid throat swabs or stool samples showing clinical manifestations of viral encephalitis; a total of 140 positive cases (9.21%) were detected, including CV-A16 2.14% (3/140), CV-A10 1.43% (2/140), CV-A6 9.29% (13/140), EV-A71 0%(0/140), and other uncategorized EVs 87.14% (122/140). Among the 140 cerebrospinal fluid EV-positive children, 32 had typical hand-foot-mouth disease or herpetic angina, and 108 had only fever and upper respiratory tract infection. Real-time fluorescence quantitative PCR detection and virus typing can greatly improve the diagnosis rate of EV. Multi-sample EV nucleic acid detection and virus typing in children with viral encephalitis effectively improve the etiological diagnosis rate. Nonetheless, the development of multivalent vaccines remains the most economical and effective measure to prevent and control EV infection.